The Noisy Monopolist: Imperfect Information, Price Dispersion and Price Discrimination - Salop, Steven (Review of Economic Studies, 1977)
Journal Article The Noisy Monopolist: Imperfect Information, Price Dispersion and Price Discrimination Get access Steven Salop Steven Salop Federal Reserve Board Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 44, Issue 3, October 1977, Pages 393–406, https://doi.org/10.2307/2296898 Published: 01 October 1977 Article history Received: 01 April 1974 Accepted: 01 October 1976 Published: 01 October 1977